1987
DOI: 10.1007/bf01880167
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methods for determining adverse impacts of air pollution on terrestrial ecosystems

Abstract: Methods used to determine adverse impacts of air pollution on four levels of biological organization of terrestrial ecosystems were evaluated for their use in decision making by federal land managers of class I areas and as guidelines for scientists employed to design field studies in these areas. At the level of the individual, visible injury, biomass, and sulfur uptake were the most often used components; at the population level, natality and mortality; at the community level, diversity; and at the ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Quite expectedly, the effect sizes based on species number and diversity data were strongly correlated (for vascular plants r = 0.73, n = 12 studies for which both values were available, P = 0.007), and therefore we selected species richness as the principal response variable. This selection was based both on the conclusion by Sigal and Suter (1987) that species richness is a more consistent measure of pollution effects than species diversity, and on the larger amount of the available data. For one study that reported only plant diversity (Galbraith et al ., 1995), we calculated the changes in species richness by using regression equations built on data from studies in which both species number and diversity data were available.…”
Section: Methodsmentioning
confidence: 99%
“…Quite expectedly, the effect sizes based on species number and diversity data were strongly correlated (for vascular plants r = 0.73, n = 12 studies for which both values were available, P = 0.007), and therefore we selected species richness as the principal response variable. This selection was based both on the conclusion by Sigal and Suter (1987) that species richness is a more consistent measure of pollution effects than species diversity, and on the larger amount of the available data. For one study that reported only plant diversity (Galbraith et al ., 1995), we calculated the changes in species richness by using regression equations built on data from studies in which both species number and diversity data were available.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, any critical level for natural vegetation must be considered as exceeded when a change in the frequency of species or genotypes occurs (Reiling & Davison, 1992b). However, air pollutants such as ozone may directly affect individual organisms, and the response of a plant community to ozone is the result of the sum of primary effects on its individuals which can result in alterations of plant performance in competition (Sigal & Suter, 1987). Therefore understanding the relative susceptibilities of single species and single genotypes to ozone remains an absolute prerequisite for estimating effects at the community level.…”
mentioning
confidence: 99%
“…It requires information on technical scientific issues as well as input from resource managers. Furthermore, guidelines must be developed in the absence of all the data that would be desirable for decision-making (Sigal and Suter 1987).…”
Section: Ancmentioning
confidence: 99%